Two center and Coulomb effects in near-threshold ionization of H+ 2 by short laser pulses - Ciappina, Marcelo Fabián (2009)
We investigate the influence of the Coulomb potential as well as the two center contribution in the angle-resolved photoelectron spectrum, resulting from the single ionization of H[image omitted] molecules by short laser pulses. We present an extension of the Coulomb-Volkov distorted wave approximation to the H[image omitted] case. This last model can be considered as an improvement beyond the strong-field approximation (SFA) and was capable of reproducing the structures present in near-threshold ionization in atoms.